of, and, in, the, as, a, for, th Application of Parallel Importation and Voluntary License in the Covid-19 Vaccines Patent as a Strategy for Handling the Health Emergency Situations in Indonesia - Kukuh Tejomurti; Pujiyono Pujiyono; Pranoto Pranoto; Umi Khaerah Pati (Hang Tuah Law Journal, 2020)
This article examines how the application of Parallel Importation and Voluntary License in the Application of the Covid-19 Vaccine Patent as a Strategy for Handling Health Emergency Situations in Indonesia. The problem of the Covid-19 vaccine happens in many countries around the world, including Indonesia whos trying to find a vaccine that can neutralize the Covid-19 Virus. As a consequence of the tremendous demand for vaccines, the world pharmaceutical industry is encouraged to provide Covid-19 vaccines for the needs of 7.8 billion. This article uses normative legal research with a statute, conceptual, and comparative law approach. The results showed that mechanisms such as parallel importation and voluntary licenses could be reached to procure the Covid-19 vaccine. If parallel importation and voluntary licenses are not successful, then the Government shall take a win-lose approach, such as Compulsory Licensing and Use of Patents by the Government, or initiate an anti-monopoly lawsuit.